2014
DOI: 10.1093/rpd/ncu165
|View full text |Cite
|
Sign up to set email alerts
|

Protein biomarkers for enhancement of radiation dose and injury assessment in nonhuman primate total-body irradiation model

Abstract: Development and validation of early-response radiation injury biomarkers are critical for effective triage and medical management of irradiated individuals. Plasma protein and haematological profiles were evaluated using multivariate linear-regression analysis to provide dose-response calibration curves for photon-radiation dose assessment in 30 rhesus macaques total-body-irradiated to 1-8.5 Gy with (60)Co gamma rays (0.55 Gy min(-1)). Equations for radiation dose received were established based on different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…Gastrointestinal effects are prominent at doses greater than 5–6 Gy and progress more rapidly, while neurovascular collapse ensues at doses greater than 10–20 Gy which occurs immediately [2,3]. Rapid and early diagnosis is essential as demonstrated by the dramatic increase in survival rates if treatments are administered within few days after exposure [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal effects are prominent at doses greater than 5–6 Gy and progress more rapidly, while neurovascular collapse ensues at doses greater than 10–20 Gy which occurs immediately [2,3]. Rapid and early diagnosis is essential as demonstrated by the dramatic increase in survival rates if treatments are administered within few days after exposure [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Elevation of several acute phase proteins in WBI mice indicated rapid systemic inflammatory response possibly due to damage of vascular endothelial cells. Interestingly, some cytokines (IL6) and acute response proteins (CRP) reported to show radiation-responsive profile [27] were not identified in our serum exosomes analysis suggesting that exosome analysis can be restrictive and may miss important cues otherwise detectable in whole serum analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression profiles of several individual protein biomarkers have been examined for their relationship to received radiation dose and exposure pattern. In a TBI nonhuman primate (NHP) model, dose-dependent increases in CRP, SAA, FIT3 Ligand (FL), Interleukin-6 (IL6) and amylase were observed in the peripheral blood ( 2830 ). Similar changes in expression were seen in plasma for SAA, FL, IL6 and G-CSF in TBI mice models ( 3133 ).…”
Section: Proteomicsmentioning
confidence: 99%
“…Compared to traditional cytogenetic techniques, hematological markers are faster and utilize existing high-throughput methodologies. In several studies, it has been reported that a combined approach using analysis of blood cell populations with concurrent measurement of serum-soluble protein biomarkers shows a strong correlation between predicated and actual received dose in mouse and NHP models (28, 29, 31, 33, 91). In addition, successful use of a multivariate approach in the clinical management of victims of the Dakar radiation accident was reported, in which 63 individuals were screened to determine the level of radiation exposure using a combination of classic cytogenetic biodosimetry, evaluation of blood cell population and measurement of FL.…”
Section: Lymphocyte Kinetics/clinical Exammentioning
confidence: 99%